Value of college athletic programmes in the Korean Higher Education: A contingent valuation study. (25th July 2019) - Cha, Jae Hyuk; Lee, Jungmin; Kim, Taehee; Chang, Kyungro
Abstract: Higher Education institutions in Korea are undergoing restructuring in response to the government reform policy. As one aspect of the restructuring, many colleges are reducing or abolishing the athletic programmes. This study investigated the value of athletic programmes for college students by using the contingent valuation method. The results of a multivariate survival analysis with a convenience sample of 372 undergraduate students indicate that the monetary value of the willingness of a student to pay for athletic programmes was about KRW 116, 000 per semester. Students' level of involvement with and knowledge about intercollegiate athletics, as well as monthly allowance and year in college have positive effects on willingness to pay for athletic programmes. 초록: 한국의 대학들은 최근 정부의 교육개혁 정책에 때라 구조조정을 추진하고 있다. 구조조정의 한 정책으로 많은 대학들은 대학 운동부를 축소하거나 폐지하고 있다. 이에 본 연구에서는 조건부 가치측정법을 활용하여 대학생들이 인식하는 대학 운동부의 가치를 평가하고자 한다. 372명의 학부 대학생들을 대상으로 다변량 생존분석을 실시한 결과 대학생들이 대학 운동부의 존속을 위해 기꺼이 지불하고자 하는 금액은 학기당 약 116, 000원으로 나타났다. 학생들의 대학 스포츠에 대한 관여도와 지식, 한달 용돈, 그리고 학년은 대학 운동부의 존속을 위한 지불의사에 긍정적인 영향을 미치는 것으로 나타났다.